2021
DOI: 10.1111/jog.14725
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin on homocysteine levels in patients with polycystic ovary syndrome: A systematic review and meta‐analysis

Abstract: Purpose Metformin is widely used as an insulin sensitizer in polycystic ovary syndrome (PCOS) patients. However, previous studies have found that the effect of metformin on the level of homocysteine were not consistent in PCOS patients. The aim of this review was to analyze the effect of metformin on homocysteine levels in patients with PCOS patients. Methods The Cochrane Library, Pubmed, and Web of Science were searched according to predefined search terms. There is no restriction for publication time and lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…On the contrary, Esmaeilzadeh et al found a significant decrease in the mean B12 level in patients after six months of metformin 1 g/day treatment (456.88 ± 172.32 to 367.69 ± 28.10 pg/mL; P = 0.002) [ 23 ]. In a meta-analysis, including these four studies, Li et al showed no significant change in vitamin B12 levels before and after metformin treatment (mean difference 24.70 pg/mL; 95% confidence interval [CI] −22.54 to 71.93; P = 0.31; moderate heterogeneity [ I 2 = 74%]) [ 24 ]. Treatment with metformin was followed by a decline in B12 levels in studies by Greibe et al (1.5-2.5 g/day for six months) and Khalil et al (1.5 g/day for 16 weeks) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Esmaeilzadeh et al found a significant decrease in the mean B12 level in patients after six months of metformin 1 g/day treatment (456.88 ± 172.32 to 367.69 ± 28.10 pg/mL; P = 0.002) [ 23 ]. In a meta-analysis, including these four studies, Li et al showed no significant change in vitamin B12 levels before and after metformin treatment (mean difference 24.70 pg/mL; 95% confidence interval [CI] −22.54 to 71.93; P = 0.31; moderate heterogeneity [ I 2 = 74%]) [ 24 ]. Treatment with metformin was followed by a decline in B12 levels in studies by Greibe et al (1.5-2.5 g/day for six months) and Khalil et al (1.5 g/day for 16 weeks) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is the most common endocrine disorder and one of the most frequent causes of infertility in women [ 1 ]. It affects 5–20% of women of childbearing age [ 1 , 2 ]. Diagnosing PCOS is challenging due to the variability of symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%